Unstable Distal Radius Fractures: Restoration of the Radial Length with Use of Special Palmar Fixed-angle Plate - Qu, Y.; Xu, J.; Jiang, T.; Zhao, H.; Gao, Y.; Hou, W. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2013)
To describe the radiological and clinical outcome of unstable distal radius fractures treated with use of a palmar locking plate designed especially to restore the length of the radius.19 patients (6 men and 13 women) with an average age of 55 (23–71) years with an unilateral unstable distal radius fracture were treated with open reduction and internal fixation with use of an special palmar locking plate. In the distal long hole of this plate a longitudinal gear drive mechanism is integrated, in which a digital knob device consisting of a handle with a serrated ring is inserted. By turning the handle the distal fragments which are fixed to the plate by locking screws are pushed distally with respect to the shaft fragment until the correct length of the radius is restored. The patients were followed for 12 months. During last follow-up, standard radiography, functional results and pain scores were assessed.All fractures united uneventfully with no secondary displacement, and no superficial or deep infection. Ulna variance measured on average – 0.8±1.5 mm. Wrist extension averaged 63°, wrist flexion averaged 59°. Grip strength averaged 82% of the contralateral uninjured side.The used special gear drive plate allows accurate restoration of the length of the radius even in unstable fractures with good clinical results.
Keywords: unstable distal radius fracture; palmar locking plate; gear drive plate